Rapid review protocol: Zinc for the prevention or treatment of COVID-19 and other coronavirus-related respiratory tract infections - Hunter, Jennifer (Integr Med Res, 2020)
BACKGROUND: The global COVID-19 pandemic has prompted an urgent search for effective interventions. SARS-CoV-2 mortality/morbidity risk increases with age and for those chronic disease co-morbidities, both of which are associated with lower zinc status, as is the risk of infection. METHODS: Rapid review methods will be applied to a systematic review of zinc for the prevention or treatment of SARS-CoV-2 and viral respiratory tract infections in humans. Included are published studies reporting randomised and quasi-randomised controlled trials that compare zinc intervention to placebo and/or other comparator interventions. English and Chinese language databases will be searched for primary studies of viral respiratory tract infections and clinical trial registries for SARS-CoV-2 infections. Due to concerns about indirectness, studies evaluating non-SARS-CoV-2 coronavirus infections will be rated down by one level, and non-specific or confirmed non-coronavirus viral infections will be rated down by two levels. Review constraints include (1) using Google translate when screening articles published in languages other than English or Chinese and limited translation (2) following calibration, only one reviewer will screen articles, extract data, appraise quality and conduct the analysis, (3) prioritising data extraction and meta-analyses of SARS-CoV-2 studies and critical outcomes of other viral infections, followed by high risk groups and (4) reporting important preliminary findings prior to peer review if necessary. DISCUSSION: The application of these rapid review methods and broadening the inclusion criteria to include other coronavirus-related viral respiratory tract infections aims to enable a timely evidence appraisal of priority research questions and dissemination of results. STUDY REGISTRATION: PROSPERO CRD42020182044.